2007
DOI: 10.2134/agronj2006.0056
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Irrigation and Fall Dormancy Effects on Alfalfa Productivity in a Semiarid, Subtropical Climate with a Bimodal Precipitation Pattern

Abstract: Alfalfa (Medicago sativa L.) is an important hay crop produced under rain‐fed conditions or various levels of irrigation in the southern Great Plains of the USA. The objective of this study was to determine the role of fall dormancy (FD) on productivity and forage nutritive value of alfalfa in rain‐fed and supplemental irrigation systems in a semiarid, subtropical climate with a bimodal pattern of precipitation. Cultivars with FD ratings of 1 to 3 (dormant), 4 to 6 (moderately dormant), and 7 to 8 (nondormant)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…These results agreed with those of Kallenbach et al (2002), who reported higher CP and lower NDF for a very dormant cultivar (FD 2) compared to two dormant cultivars (FD 4) in Missouri. Our findings also concurred with those from a study conducted in Texas by Malinowski et al (2007) that reported a narrow decline of CP across several FD groupings with dormancy rating ranging from 1 to 8. Differences in CP between harvest regimes observed in the second and the third year were consistent with differences in fiber traits but opposite in nature (Table 6; Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results agreed with those of Kallenbach et al (2002), who reported higher CP and lower NDF for a very dormant cultivar (FD 2) compared to two dormant cultivars (FD 4) in Missouri. Our findings also concurred with those from a study conducted in Texas by Malinowski et al (2007) that reported a narrow decline of CP across several FD groupings with dormancy rating ranging from 1 to 8. Differences in CP between harvest regimes observed in the second and the third year were consistent with differences in fiber traits but opposite in nature (Table 6; Fig.…”
Section: Resultssupporting
confidence: 91%
“…Differences in nutritional value were detected among cultivars within FD ratings (Tables 2 and 3); however, the focus of this study was on FD effects. Therefore, differences among cultivars within FD rating effects will not be discussed, although the data are presented in Table 3 for supplemental information, as in other published studies reporting only FD rating means (Malinowski et al, 2007; Lauriault et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Differences among cultivars within FD categories were detected for most of the traits studied (Table 2), however the focus of the present study was on FD rating. Therefore, the effects of cultivars within a FD category are not discussed, as in other studies investigating FD groupings (Malinowski et al, 2007; Lauriault et al, 2009; Rimi et al, 2012). With the exception of stand density, the analysis of variance revealed significant interactions between harvest regimes and sampling dates for all the traits studied (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The FD rating, or FD category, influences agronomic performance of alfalfa in several ways, including productivity (Volenec, 1985; Ventroni et al, 2010), nutritive value (Malinowski et al, 2007; Rimi et al, 2012), plant survival (Kallenbach et al, 2002; Cunningham et al, 2003), and root characteristics (Cunningham et al, 1998; Haagenson et al, 2003b). Alfalfa cultivars are grouped into 11 FD categories based on regrowth potential in the autumn, with FD = 1 representing those going dormant earliest and FD = 11 representing those cultivars being the tallest, and least dormant, in the fall (Teuber et al, 1998).…”
mentioning
confidence: 99%
“…The traits of alfalfa as a deep‐rooted, N‐fixing, perennial legume may favor its potential use in rainfed grasslands as producers retire some cropland from irrigation. However, producers in the southern High Plains should consider WUE while selecting an alfalfa cultivar (Lindenmayer et al., 2011) in addition to persistence, quality, disease, and insect pest resistance (Malinowski, Pinchak, Kramp, Zuo, & Butler, 2007). In a study conducted in New Mexico under irrigated conditions, Lauriault et al.…”
Section: Introductionmentioning
confidence: 99%